Kevin Rudd, celebrity and audience democracy in Australia. (February 2014) - Wilson, Jason
Kevin Rudd's political ascendancy moved celebrity personae and celebrity media closer to the central terrain of Australian politics. This tended to diminish the authority of political journalists, and presented a directed challenge to the power of bureaucrats and activists in the Australian Labor Party (ALP). Rudd's engagement with celebrity culture, and his instantiation of 'audience democracy' can be understood in the context of Australia's 'post-broadcast democracy', the competitive, co-adaptive dynamic between political actors and journalists, and the increasing celebritisation of contemporary culture. In responding to Rudd's strategies, political journalists resorted to the 'scourging' tactics familiar from celebrity journalism. Rudd's brief Prime Ministership raises questions about the future of politics and journalism in celebritising, post-broadcast democracies, that have global ramifications.